Recall bias, MMR, and autism. Issue 6 (1st December 2002) - Andrews, N; Miller, E; Taylor, B; Lingam, R; Simmons, A; Stowe, J; Waight, P
Abstract : Parents of autistic children with regressive symptoms who were diagnosed after the publicity alleging a link with measles, mumps, and rubella (MMR) vaccine tended to recall the onset as shortly after MMR more often than parents of similar children who were diagnosed prior to the publicity. This is consistent with the recall bias expected under such circumstances.